THEORY AND CONCEPT SOCIALIZATION ENTREPRENEUR COMPETENCE - Dwi Nugrono; Wahyono Saputro (Universitas Katolik Widya Karya Malang, 2023)
Competency is the ability of each individual’s work that includes aspects of knowledge, skills and work attitudes in accordance with the established standards (BNSP 2015) and sanctions on the limits / definitions used in UU No.13 Tahun 2013.